Framework for advancing water resource sustainability and climate resilience through local-scale hydrological modeling in the Ganges Delta - Jampani, Mahesh; Sena, Dipaka Ranjan; Matheswaran, Karthikeyan (International Water Management Institute, 2023)
The Ganges Delta has large agricultural landscapes that provide food for millions of people. However, changes in climate and anthropogenic activities are causing water scarcity, floods and soil salinization, threatening food security and putting livelihoods at risk. To address these challenges, the CGIAR Initiative on Asian Mega-Deltas (AMD) is working to create more resilient, inclusive and productive deltas that can adapt to climate change and other stressors. The International Water Management Institute (IWMI) is undertaking local-scale hydrological modeling and developing Artificial Intelligence (AI)-powered salinity forecasting in the Ganges Delta Region to evaluate water and salinity dynamics. This innovation brief outlines the methodological framework that will be used to develop a salinity forecasting system for the polders in Bangladesh using machine learning techniques, surface water and groundwater flow, and contaminant transport modeling to understand water and salinity dynamics and balances in the respective polders. The overall aim is to generate polder-specific knowledge that can optimize water management, increase agricultural productivity and ensure the long-term sustainability of this crucial deltaic system.